(untitled) (Praxis Educativa, 2012)
This article fits within the framework of the Research Project called “Teachers’ Education Program V: Memorable teachers´ biographies. Great Teachers, Intellectual Passions and Professional Development” (2012-2013) carried out by the Educational and Cultural Studies Research Group (GIEEC) at the School of Humanities, in Mar del Plata State University. Within it, and from a biographical-narrative perspective, narrations from teachers who are considered memorable are recovered, in order to identify moral values inherent to the ethical dimension essential to their passion for teaching. In this case, we resort to philosophy, on the one hand, to revise its contributions to the biographical-narrative research area in education and on the other, to make views related to the concept of otherness explicit. In this regard, we are interested in the meaning and sense that memorable teachers place in the idea of otherness in their teaching practices, since this is an ethical concept par excellence.